2017
DOI: 10.3346/jkms.2017.32.6.926
|View full text |Cite
|
Sign up to set email alerts
|

Regional Difference of Causative Pollen in Children with Allergic Rhinitis

Abstract: The aim of this study was to investigate role of common pollen in Korean school-aged children with allergic rhinitis (AR) in 5 provinces (Incheon Metropolitan City-Gyeonggi Province, Chungcheongbuk-do, Gwangju Metropolitan City, Busan Metropolitan City, and Jeju Special Self-Governing Province), using a questionnaire and skin prick test, and to assess the differences among the residential regions. Among the enrolled 14,678 total children, 1,641 (22.0%) had AR. The sensitization rate to pollen (38.7%) was the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…Additionally, the sensitization rate to pollen has been one of major aeroallergen to children with allergic disease such as asthma and AR [ 3 , 4 ]. The allergen sensitization rate to pollen was 16.5% (control) and 21.9% (chronic cough), which was the second-highest among examined allergens in the present study, lower than reported in the previous study from school-aged children with AR [ 17 ]. It is well-known that pollen and HDM allergens induce Th2 immune responses, but pollen grains contain other immunomodulatory substances that differentiate them from HDM [ 18 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, the sensitization rate to pollen has been one of major aeroallergen to children with allergic disease such as asthma and AR [ 3 , 4 ]. The allergen sensitization rate to pollen was 16.5% (control) and 21.9% (chronic cough), which was the second-highest among examined allergens in the present study, lower than reported in the previous study from school-aged children with AR [ 17 ]. It is well-known that pollen and HDM allergens induce Th2 immune responses, but pollen grains contain other immunomodulatory substances that differentiate them from HDM [ 18 ].…”
Section: Discussioncontrasting
confidence: 82%
“…The rates and types of common aeroallergen sensitization vary widely across countries, and studies conducted in the same country have reported different results [1,2,22]. Studies on sensitization to aeroallergens in Koreans have also shown very different results depending on the test method, type of aeroallergen, region, and subject selection (Table 4) [9][10][11][12][13][14][15][16][17][18][19][20]. DP and DF showed an overwhelmingly high sensitization rate compared to other antigens, but the reported frequency of sensitization to other aeroallergens had varied from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on the status of aeroallergen sensitization in Koreans [9][10][11][12][13][14][15][16][17][18][19][20]. However, many of these studies are old, and it is difficult to consider them representative of the national situation as only a limited number of aeroallergens were investigated, or relatively few patients were enrolled at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen and fungal allergy is a regionally variable disease driven by numerous environmental factors, including local flora, weather, climate, and air pollution. [15][16][17] As a result, the allergenic content of the atmosphere varies not only among countries but even in the same country, depending on the climate (temperature, winds, rains, and humidity), geography, vegetation, and cultural factors. 8,18,19 Pollen calendars have been constructed in many countries to keep track of the pollen variety and concentration of airborne pollens.…”
Section: Introductionmentioning
confidence: 99%